Factors Affecting the Propensity to Create Budgetary Slack Evidence from Vietnamese Enterprises - Trinh, Hiep Thien (University of Economics Ho Chi Minh City, 2023)
Budgeting is widely advertised as an effective managerial accounting tool but has been criticized mainly for budgetary slack reason. The purpose of this article is therefore to empirically examine relationships between budget participation, budget emphasis, risk awareness, private knowledge and the propensity to create budgetary slack. This study also extends the previous research by testing the hypothesized effect of the nonfinancial managerial accounting information use on various factors associated with the propensity to create budgetary slack. A survey data from 243 Vietnamese enterprises was used to conduct a structural equation modeling analysis. The results indicate that budget participation and budget emphasis incrementally affect the propensity to create budgetary slack while nonfinancial managerial accounting information is fairly useful to limit human aspects of budgeting. In addition, no correlation between private knowledge and creation of budgetary slack by subordinates was found. Once again, the results of this research confirm the effects of human factors in budgeting, which measured in a Vietnamese business environment and extended the understanding of the role of nonfinancial managerial accounting information in improving the budgeting process.